Histopathological Evaluation of Tumours And Cysts of The Epidermis and Dermal Adnexae in a Tertiary Care Hospital - Gandhi, Ramya; Vijayaraghavan, Sriram (Annals of Pathology and Laboratory Medicine, 2018)
Background: Skin tumours are a challenging group of conditions ,it is difficult to classify and these are diagnosed chiefly by histopathology. The aim of our study was to analyze the incidence and classify the histopathological pattern of tumours and cysts of the epidermis and dermal appendages. Methods: The current study was a retrospective observational study of epidermal and adnexal tumours and cysts over a period of five and half years from January2007 to December 2012 reported in the department of Pathology ,SMVMCH,Pondicherry over a 5 year period from were analysed and correlated statistically. Result: Out of 160 skin lesions 62 were found to be epidermal and dermal adnexal tumours, among these benign adnexal tumours(14%) were the commonest followed by benign epidermal tumours(12.5%) ,malignant epidermal tumours(10.5%) and malignant adnexal tumours(2%).The ratio of benign(42) to malignant(22) tumour was 1.9:1.the ratio of benign(20) to malignant(17) epidermal tumour was 1.17:1 .The ratio of benign adnexal(22) to malignant counterpart (3) was 7.3:1 and the ratio of skin tumours (62) to cystic lesion(98) was 1:1.5. The commonest epidermal tumour was seborrheic keratosis. Epidermal cysts were the commonest type of cyst in the epidermis. Common skin appendage tumours were nodular hidradenoma followed by pilomatrixoma. The common malignant tumour was basal cell carcinoma. Conclusion: Cutaneous tumours represent the complexity of the epidermal and dermal adnexae since they have a similar morphology to their cell of origin .Hence the histopathological examination is mandatory for diagnosis and categorization of these tumours.